Multivalency of PEG-thiol ligands affects the stability of NIR-absorbing hollow gold nanospheres and gold nanorods. Issue 16 (11th April 2016) - Ruff, J.; Steitz, J.; Buchkremer, A.; Noyong, M.; Hartmann, H.; Besmehn, A.; Simon, U.
Abstract : In this work the effect of multivalency on the stability of NIR-absorbing HAuNSs and AuNRs functionalized by mono-, bi- and tridentate polyethyleneglycol (PEG) thiol ligands is reported. Abstract : In this work the effect of multivalency on the stability of NIR-absorbing HAuNSs and AuNRs functionalized by mono-, bi- and tridentate polyethyleneglycol (PEG) thiol ligands is reported. Comparison of commercially-available monodentate and self-synthesized bi- and tridentate methoxy terminated thiol-polyethyleneglycol ligands having molecular weights of around 5000 Da shows the stability increase of HAuNSs and AuNRs for bi- and tridentate ligands, attributed to the multivalency of the ligands. The stability was explored according to three different aspects: (1) stability towards competition reactions with the strong binding ligand dithiothreitol, (2) resistance towards oxidative Au dissolution with potassium cyanide, and (3) colloidal stability, tested by the addition of NaCl. Our PEGylation approach leads to AuNRs where the CTAB concentration is below the detection limit of the performed analytical methods, which is vital for any clinical applications. Furthermore, we found strikingly high biocompatibility after PEGylation for both particle types whereby we observed no significant difference in cytotoxicity comparing the mono-, bi- and tridentate PEGylated species.